Small farmer cooperatives and voluntary coffee certifications: Rewarding progressive farmers of engendering widespread change in Costa Rica?. (May 2017) - Snider, Anna; Gutiérrez, Isabel; Sibelet, Nicole; Faure, Guy
Highlights: Voluntary certifications are widespread in Costa Rica to meet market demands. There are no consistent financial incentives for farmers to pursue certification. The structure of the certified coffee market limits farm-level change. Certifications offer non-financial benefits to both farmers and cooperatives. Abstract: Our research examines the benefits and drawbacks for cooperatives who participate in voluntary coffee certifications. We interviewed administrators at twenty Costa Rican coffee cooperatives about management practices related to voluntary certification. Voluntary certifications are popular among coffee cooperatives. Access to certified markets is facilitated by state support of the cooperative sector, regulation of the coffee sector and well-enforced environmental and social laws. However, there are no significant or consistent financial incentives for farmers to pursue certification. Multiple certifications may lower auditing and implementation costs, but cooperatives rarely receive the full premium for multiply-certified coffee. Low market demand for certified coffee, weak price incentives and high auditing and management costs encourage cooperatives to certify only a portion of their members. This strategy rewards compliant farmers rather than inducing widespread change to farming practices among the entire membership. Though financial incentives are weak, certifications offer non-financial benefits to both farmers and cooperatives, including better management and more resilient cooperatives.